1984
DOI: 10.1289/ehp.8455179
|View full text |Cite
|
Sign up to set email alerts
|

Elastin metabolism and chemistry: potential roles in lung development and structure.

Abstract: Elastic fibers are important for elasticity and extensibility of lung tissue. In the developing lung, elastic fibers appear in greatest numbers during the process or period of alveolarization. A variety of mesenchymal cells in lung appear responsible for elastin synthesis. Elastin is a novel protein both from the standpoint of its processing into elastic fibers and chemical properties. For example, elastin undergoes posttranslational modification before its assembly into fibers. These steps include limited pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
2

Year Published

1994
1994
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(39 citation statements)
references
References 102 publications
0
37
2
Order By: Relevance
“…The age-dependent accumulation of modified aspartic acid residues is a common feature in ageing elastin regardless of the tissue source. In fact, in healthy adult tissues, elastin production is suppressed by a post-transcriptional mechanism mediating a rapid decay of the tropoelastin mRNA [14,35], however, re-initiation of elastin production has been observed after tissue damage [30]. This is apparently a contradiction to the assumption that elastin is a permanent protein without relevant turnover, as indicated by the AAR data.…”
Section: Aar In Purified Elastin From Arteriesmentioning
confidence: 77%
See 1 more Smart Citation
“…The age-dependent accumulation of modified aspartic acid residues is a common feature in ageing elastin regardless of the tissue source. In fact, in healthy adult tissues, elastin production is suppressed by a post-transcriptional mechanism mediating a rapid decay of the tropoelastin mRNA [14,35], however, re-initiation of elastin production has been observed after tissue damage [30]. This is apparently a contradiction to the assumption that elastin is a permanent protein without relevant turnover, as indicated by the AAR data.…”
Section: Aar In Purified Elastin From Arteriesmentioning
confidence: 77%
“…This is apparently a contradiction to the assumption that elastin is a permanent protein without relevant turnover, as indicated by the AAR data. Newly synthesised elastic fibres have been described as highly disorganised, non-cross-linked, immature, and of a low elastin content [30]; these incomplete fibres should be removed by the purification steps employed (see also [17]). It is an interesting, but as yet unsolved question, whether the accumulation of post-translationally modified elastin molecules with age has functional implications for the elasticity of the artery wall.…”
Section: Aar In Purified Elastin From Arteriesmentioning
confidence: 99%
“…4.3.2 Elastin synthesis: Elastin is another protein of the connective tissue; it is different from collagen, but its content of glycine is also about 33% (Boudier et al 1981). From data on elastin content in different tissues (Lowry et al 1941;Neuman and Logan 1950;Rosenbloom et al 1993), the total elastin in the human body can be estimated as about 75 g. It is usually considered to turn over very slowly, however, about 1-2% per year in the total human body (Rucker and Dubick 1984;Shapiro et al 1991), though there have been reports of turnover as high as 455 mg/day in aortic tissue, which would mean an average lifetime of about 11 days (Keeley and Johnson 1983). Clearly, further work is needed to resolve the major discrepancy in estimates, and to establish the true rate of turnover.…”
Section: Synthesis Of Proteinsmentioning
confidence: 99%
“…The focus has generally been directed towards quantification of proteins such as elastin and collagens or cells such as neutrophils and macrophages which are known to be important for the lung milieu [1,33,64,102]. The quantity of structural proteins is important in the pathology of PF; however, the amounts of proteases and protease inhibitors are just as relevant [64,103].…”
Section: Protein Quantity In the Progression Of Pfmentioning
confidence: 99%
“…Other studies have also demonstrated that elastic fibres were present in the same quantity in lung ECM that was damaged and then repaired as compared to non-damaged lung ECM, but the distribution was still disordered after the repair process [102,121]. …”
Section: Protein Quality In the Progression Of Pfmentioning
confidence: 99%